2018
DOI: 10.1002/glia.23553
|View full text |Cite
|
Sign up to set email alerts
|

p75NTR regulates brain mononuclear cell function and neuronal structure in Toxoplasma infection‐induced neuroinflammation

Abstract: Neurotrophins mediate neuronal growth, differentiation, and survival via tropomyosin receptor kinase (Trk) or p75 neurotrophin receptor (p75 NTR ) signaling. The p75 NTR is not exclusively expressed by neurons but also by certain immune cells, implying a role for neurotrophin signaling in the immune system. In this study, we investigated the effect of p75 NTR on innate immune cell behavior and on neuronal morphology upon chronic T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 73 publications
7
59
0
Order By: Relevance
“…Finally, there may be other, as yet undetermined, signals that induce monocyte infiltration into the brain as a consequence of T. gondii infection but not as a direct response to the invading parasites. In chronic T. gondii models, Ly6C hi monocytes infiltrating the CNS do not express classic markers of phagocytic cells, such as TREM2 and F4/80 (23,54), although it has been shown that Ly6C hi cells can differentiate into more phagocytic Ly6C lo cells, with the potential to contribute directly to parasite clearance (23,55). Ly6C hi cells were detected in both the hippocampus and the cortex during chronic infection (23,55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there may be other, as yet undetermined, signals that induce monocyte infiltration into the brain as a consequence of T. gondii infection but not as a direct response to the invading parasites. In chronic T. gondii models, Ly6C hi monocytes infiltrating the CNS do not express classic markers of phagocytic cells, such as TREM2 and F4/80 (23,54), although it has been shown that Ly6C hi cells can differentiate into more phagocytic Ly6C lo cells, with the potential to contribute directly to parasite clearance (23,55). Ly6C hi cells were detected in both the hippocampus and the cortex during chronic infection (23,55).…”
Section: Discussionmentioning
confidence: 99%
“…In chronic T. gondii models, Ly6C hi monocytes infiltrating the CNS do not express classic markers of phagocytic cells, such as TREM2 and F4/80 (23,54), although it has been shown that Ly6C hi cells can differentiate into more phagocytic Ly6C lo cells, with the potential to contribute directly to parasite clearance (23,55). Ly6C hi cells were detected in both the hippocampus and the cortex during chronic infection (23,55). Additionally, in a mouse model of Alzheimer's disease, chronic T. gondii infection resulted in increased clearance of plaque-forming Aβ, an outcome attributed to the phagocytic contribution of Ly6C hi monocytes (54).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have reported that proBDNF signaling regulates the monocyte/macrophage/microglia functions and contributes to inflammatory responses in spinal cord injury, infection, or chemical insults. [7][8][9]26 However, all of the studies are from animal experimental studies, thus it is necessary to identify the immune-modulatory role of proBDNF in the inflammatory diseases in human. In the cultured human PBMCs and monocytes systems, our study demonstrated that proBDNF regulated the functions of monocytes and contributed to the disease progress of AAD.…”
Section: Discussionmentioning
confidence: 99%
“…In the spinal cord injury mouse model, proBDNF was found to play a detrimental role in spinal injury by regulating ED1 + macrophage infiltration and migration . In addition, in Toxoplasma infection‐induced neuroinflammation, proBDNF signaling in macrophage/microglia contributes to the recruitment of peripheral immune cells to the brain . ProBDNF and p75 NTR are highly upregulated in the peripheral blood mononuclear cells (PBMCs) of patients with major depressive disorder and in patients with alcoholism .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation